What matters for the GVC entry and exit of manufacturing SMEs in the Philippines? - Adrian R. Mendoza (Asian Development Bank Institute (ADBI), 2020)
This study explores firm-level data from the Philippines to uncover new stylized facts about the participation of manufacturing small and medium enterprise (SMEs) in global value chains (GVCs). The empirical analysis shows that manufacturing SMEs are weakly connected to foreign markets, especially to GVCs. Compared to large manufacturers, SMEs also trade fewer products with a smaller set of foreign partners. The evidence also suggests that self-selection into exporting and importing may be more relevant for SMEs than for large manufacturers. The logistic regressions partly support this view, with TFP being a significant contributor to the GVC entry of SMEs but not of large manufacturers. In general, the factors driving GVC entry are not exactly the same for small and large manufacturers. For large firms, employment size and R&D are significant. On the other hand, age and TFP seem to be the variables that uniquely determine the GVC participation of Philippine SMEs. Foreign ownership, past importing activities, and proximity to economic zones can be considered universal factors important to all establishments. The regressions also indicate that SMEs may be disproportionately affected by changes in the policy environment. Finally, the results highlight some asymmetries in the factors that affect the GVC entry and exit of manufacturing SMEs. Only size and foreign ownership make significant positive contributions to survival.
Keywords: F14; F23; L20; L25; 330; SMEs; Philippine manufacturing; global value chains; firm entry and exit